2020
DOI: 10.1038/s41598-020-61696-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Mediated Seed Priming Improves Germination, Growth, Yield, and Quality of Watermelons (Citrullus lanatus) at multi-locations in Texas

Abstract: Seed priming uses treatments to improve seed germination and thus potentially increase growth and yield. Low-cost, environmentally friendly, effective seed treatment remain to be optimized and tested for high-value specialty crop like watermelon (Citrullus lanatus) in multi-locations. this remains a particularly acute problem for triploids, which produce desirable seedless watermelons, but show low germination rates. in the present study, turmeric oil nanoemulsions (tne) and silver nanoparticles (AgNPs) synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
108
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(131 citation statements)
references
References 43 publications
3
108
0
1
Order By: Relevance
“…Methylcellulose nanoemulsion as a seed invigorate has improved the growth of maize seedling by increasing the root and shoot length by 18% and 33%, respectively [ 100 ]. Seed priming with turmeric nanoemulsion has resulted in better germination growth of watermelons [ 117 ]. The combination of pectin with neem oil nanoemulsion exhibit growth promotion to the soybean seeds [ 118 ].…”
Section: Optimization and Characterization Of Nanoemulsion-based Amentioning
confidence: 99%
“…Methylcellulose nanoemulsion as a seed invigorate has improved the growth of maize seedling by increasing the root and shoot length by 18% and 33%, respectively [ 100 ]. Seed priming with turmeric nanoemulsion has resulted in better germination growth of watermelons [ 117 ]. The combination of pectin with neem oil nanoemulsion exhibit growth promotion to the soybean seeds [ 118 ].…”
Section: Optimization and Characterization Of Nanoemulsion-based Amentioning
confidence: 99%
“…Recently, many methods have been adopted for the synthesis of silver oxide (Ag 2 O) NPs, namely, reduction in chemical, photochemical, and solutions reaction in thermal decomposition; reverse micelles of Ag compounds; radiation-assisted, electrochemical biosynthesis; and biosynthesis using living-plant systems. [7][8][9][10] Because of the potential applications for the development of new skills, research in this area has extended to the synthesis of semiconductor and metal NPs.…”
mentioning
confidence: 99%
“…Yang et al found that low light intensity significantly influenced the sucrose and galactosyl-sucrose oligosaccharide metabolism in both melon fruits and leaves [ 40 ]. In melons, the levels of amino acids and antioxidants vary with growing conditions and genotypes [ 41 , 42 , 43 , 44 ]. Therefore, qualitative and quantitative analyses of fruits grown in different locations are essential for quality control and the production of improved varieties.…”
Section: Introductionmentioning
confidence: 99%